Islamic Education in the New Order Period, Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University - Muhammad Ro’yi Alfadhili Nasution; Kimlansyah Romadon Siregar; Sehat Sultoni Dalimunthe (Formosa Journal of Applied Sciences, 2023)
Islamic education is a process of guidance to humans that includes the physical and spiritual based on religious (Islamic) teachings and dogmas in order to form the main personality according to Islamic rules in his life so that one day he will obtain happiness in the hereafter. During the New Order era, education was not the main goal. The New Order chose economic improvement and development as its main goal and pursued its policies through an administrative structure dominated by the military. This type of research uses the method of literature by using the theory of Islamic Theory of the New Order Period. It can be concluded that Islamic education in Indonesia in the New Order era experienced improvements and changes in a better direction compared to the colonial era and the early era of independence and the old order.